After the Miners' Strike A39 and Cornish Political Theatre versus Thatcher's Britain: Volume 1 - Farmer, Paul (Open Book Publishers, 2023)
In this rich memoir, the first of two volumes, Paul Farmer traces the story of A39, the Cornish political theatre group he co-founded and ran from the mid-1980s to the early 1990s. Farmer offers a unique insight into A39's creation, operation, and artistic practice during a period of convulsive political and social change. The reader is plunged into the national miners' strike and the collapse of Cornish tin mining, the impact of Thatcherism and 'Reaganomics', and the experience of touring Germany on the brink of reunification, alongside the influence on A39 of writers Bertolt Brecht, John McGrath and Keith Johnstone. Farmer, a former bus driver turned artistic director, details the theatre group's inception and development as it fought to break down social barriers, attract audiences, and survive with little more than a beaten-up Renault 12, a photocopier and two second-hand stage lights at its disposal: the book traces the progress from these raw materials to the development of an integrated community theatre practice for Cornwall. Farmer's candour and humour enliven this unique insight into 1980s theatre and politics. It will appeal to anyone with an interest in theatre history, life in Cornwall, and the relationship between performance and society during a turbulent era.